2018
DOI: 10.1017/psrm.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Critical Events and Attitude Change: Support for Gun Control After Mass Shootings

Abstract: When and to what extent do crises and significant events induce changes in political attitudes? Theories of public opinion and policymaking predict that major events restructure public opinion and pry open new political opportunities. We examine the effect of major events on support for public policies in the context of the Sandy Hook Elementary School mass shooting in December 2012 using a nationally representative panel survey of US adults. Across both cross-sectional and within-subject analyses, we find no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Prominent examples from current political discussions for the persistence of political beliefs despite disconfirmatory evidence are climate-change denial (G. T. Farmer & Cook, 2013; Häkkinen & Akrami, 2014; McCright & Dunlap, 2011), the “vaccination confidence gap” (Browne, Thomson, Rockloff, & Pennycook, 2015; Larson, Cooper, Eskola, Katz, & Ratzan, 2011; Tafuri et al, 2014), and the discussion about gun control in the United States (Rogowski & Tucker, 2018).…”
Section: Characteristics Of Belief Updating In Healthy Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples from current political discussions for the persistence of political beliefs despite disconfirmatory evidence are climate-change denial (G. T. Farmer & Cook, 2013; Häkkinen & Akrami, 2014; McCright & Dunlap, 2011), the “vaccination confidence gap” (Browne, Thomson, Rockloff, & Pennycook, 2015; Larson, Cooper, Eskola, Katz, & Ratzan, 2011; Tafuri et al, 2014), and the discussion about gun control in the United States (Rogowski & Tucker, 2018).…”
Section: Characteristics Of Belief Updating In Healthy Peoplementioning
confidence: 99%
“…Authors who assume that this truth decay has increased in recent years even speak of a "posttruth" era ( Jasanoff & Simmet, 2017;Lewandowsky, Ecker, & Cook, 2017;Sismondo, 2017) or "postfactual" politics (Sayer, 2017) when characterizing the current (Western) political discourse. Prominent examples from current political discussions for the persistence of political beliefs despite disconfirmatory evidence are climate-change denial (G. T. Farmer & Cook, 2013;Häkkinen & Akrami, 2014;McCright & Dunlap, 2011), the "vaccination confidence gap" (Browne, Thomson, Rockloff, & Pennycook, 2015;Larson, Cooper, Eskola, Katz, & Ratzan, 2011;Tafuri et al, 2014), and the discussion about gun control in the United States (Rogowski & Tucker, 2018).…”
Section: Truth Decay and Posttruth: Persistence Of Political Attitudesmentioning
confidence: 99%
“…Social scientists have long been concerned with the role of significant, unexpected, or dramatic events in changing political and social behavior (Borell, 2015; Baumgartner and Jones, 1993; Sorrentino and Vidmar, 1974; Rogowski and Tucker, 2018; Boomgaarden and De Vrees, 2007). The literature, however, on event‐caused hate crimes is relatively recent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study finds that anxiety induced people to become more supportive of gun control in an attempt to mitigate risks. However, other studies show no relationship between the occurrence of mass shootings and the public's support for gun restrictions, suggesting that situational anxiety may not affect gun policy preferences (Rogowski and Tucker, 2018; Barney and Schaffner, 2019).…”
Section: Anxiety and Gunsmentioning
confidence: 99%
“…The implication is that temporal or spatial proximity to such events increases anxiety in people and anxiety may increase support for gun control. However, these findings are contested (Rogowski and Tucker, 2018; Barney and Schaffner, 2019). Experiments have also shown that exposure to stories about mass shootings can lead to increased support for gun control but have not explored the role of anxiety (McGinty, Webster, and Barry, 2013).…”
Section: Anxiety and Gunsmentioning
confidence: 99%